Effect of GnRH immunocastration on immune function in male rats - Pan, Fuqiang; Du, Huiting; Tian, Weiguo; Xie, Huihui; Zhang, Bochao; Fu, Wanzhen; Li, Yunsheng; Ling, Yinghui; Zhang, Yunhai; Fang, Fugui; Liu, Ya (Frontiers in Immunology, 2023)
This study was conducted to evaluate the effects of GnRH immunocastration on the development of immune system in rats. Seventy 20-day old SD rats were randomly assigned into 2 groups, and were administered with GnRH vaccine (immunocastrated group) or adjuvant only (control group), respectively. The development of thymus and spleen and the expression of some immune factors in the immunized rats were evaluated. The results showed that compared with the control group, CD3 +, CD4-CD8- and CD4 + CD25 + cells in the preipheral blood of immunocastrated rats were significantly reduced (P < 0.05), while CD4 + CD8-, CD4-CD8 +, CD4 + CD8 + and CD19 + CD3- cells were significantly increased (P < 0.05). IL-2, IL-4, IL-6, IL-10, IL-17 and TNF-α in serum were also significantly increased (P < 0.05), but there was no significant difference in IFN-γ level between the two groups (P > 0.05). Histological analysis showed that the thymus of rats in the two groups began to shrink gradually from 20 days of age, but the process of the immune group was significantly slower than that of the control group;The spleen index of immunized rats was significantly higher than that of the control group (P < 0.05) 6-10 weeks after the first immunization, and the red pulp lymphocytes were more dense than those of the control group. IL-2, IL-4, IL-6, IL-10, IL-17, IFN-γ and Lymphocyte markers of CD4, CD8, and CD19 mRNA in thymus and spleen of immunized rats were significantly higher than those of control rats (P < 0.05). These results suggest that GnRH immunization can delay the degeneration of thymus and promote the development of spleen at a certain time in male rats.